2020
DOI: 10.1093/infdis/jiaa155
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Transmission of Gut Microbiome and Antimicrobial Resistance Genes in Infants Exposed to Antibiotics at Birth

Abstract: Vertical transmission of maternal microbes is a major route for establishing the gut microbiome in newborns. The impact of perinatal antibiotics on vertical transmission of microbes and antimicrobial resistance is not well understood. Using a metagenomic approach, we analyzed the fecal samples from mothers and vaginally delivered infants from a control group (10 pairs) and a treatment group (10 pairs) receiving perinatal antibiotics. Antibiotic-usage had a significant impact on the main source of inoculum in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 47 publications
1
41
1
2
Order By: Relevance
“…In line with Collado et al., a significant overabundance of Parabacteroides and Bacteroides in fecal samples of children born from mothers with an excessive BMI has been reported also in another study ( Cerdò et al., 2018 ). Both these Bacteroidetes genera are microbes that may frequently be vertically transmitted from mothers to offspring ( Nayfach et al., 2016 ; Li et al., 2020 ), and for this reason, the presence of these taxa in the maternal GI microbiota may affect their presence also in newborns ( Collado et al., 2010 ). Considering vertical transmission of microbes, we found that Bacteroidetes mainly characterized the gut microbiota of vaginally delivered infants.…”
Section: Discussionmentioning
confidence: 99%
“…In line with Collado et al., a significant overabundance of Parabacteroides and Bacteroides in fecal samples of children born from mothers with an excessive BMI has been reported also in another study ( Cerdò et al., 2018 ). Both these Bacteroidetes genera are microbes that may frequently be vertically transmitted from mothers to offspring ( Nayfach et al., 2016 ; Li et al., 2020 ), and for this reason, the presence of these taxa in the maternal GI microbiota may affect their presence also in newborns ( Collado et al., 2010 ). Considering vertical transmission of microbes, we found that Bacteroidetes mainly characterized the gut microbiota of vaginally delivered infants.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of studies that have focused on the acquisition and establishment of the infants’ gut microbiome from birth ( Dahlgren et al., 2019 ; Shao et al., 2019 ; Tauchi et al., 2019 ; Li et al., 2020 ). However, it remains uncertain how the microbiome of MLPT babies develops across the early life window.…”
Section: Introductionmentioning
confidence: 99%
“…Once consumed, the association between microbes resident in the fermented product becomes much more clearly biologically relevant and intimate with human lineages via their gut microbiome. Although vertical transmission of gut microbiota in humans is gaining support (Ferretti et al 2018;Li et al 2020), it is unclear at this time if and how fermented products may alter the microbiomes of humans (see below). Nevertheless, microbial cultures handed-down generationally as heirlooms may have led to an entanglement of human and microbial lineages (Ogura 2017;Cook 2018;Flachs and Orkin 2019).…”
Section: Shared Environment and Transmission Of Lineages In Fermented Foodsmentioning
confidence: 99%